Bismuth vanadate material for electroreduction of carbon dioxide as well as preparation method and application of bismuth vanadate material

By preparing lamellar bismuth vanadate materials, the problems of high overpotential and low current density of non-precious metal catalysts in carbon dioxide electroreduction were solved, and efficient carbon dioxide conversion and formic acid production were achieved, which is suitable for industrial applications.

CN120622535APending Publication Date: 2025-09-12XIAN THERMAL POWER RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510800957.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing non-precious metal catalysts have problems of high overpotential, low current density and low Faradaic efficiency when used for the electroreduction of carbon dioxide to produce formic acid. In addition, the catalyst activity is closely related to the number of active sites, and the performance needs to be improved by increasing the specific surface area.

Method used

Bismuth salt and ammonium metavanadate are added to different solvents with surfactants, and a uniform mixed solution is formed through staged stirring reaction. Combined with hydrothermal reaction and calcination process, bismuth vanadate material with a lamellar structure is prepared, and its specific surface area and crystal structure are optimized.

Benefits of technology

The current density and Faraday efficiency of carbon dioxide electroreduction are significantly improved, and the overpotential is reduced. The material has a high specific surface area, good conductivity and chemical stability, and is suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622535A_ABST
    Figure CN120622535A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth vanadate material for carbon dioxide electroreduction and a preparation method and application, and belongs to the technical field of carbon dioxide electroreduction.The method comprises the steps that bismuth salt is dissolved in a nitric acid aqueous solution, a surfactant is added, and a mixed solution A is obtained through a stirring reaction; dissolving ammonium metavanadate in a sodium hydroxide aqueous solution, adding a surfactant, and carrying out a stirring reaction to obtain a mixed solution B; and mixing the mixed solution A and the mixed solution B, adjusting the pH value to be neutral, and carrying out stirring reaction, hydrothermal reaction, washing, drying and calcination reaction to obtain the bismuth vanadate material for carbon dioxide electroreduction. The preparation method comprises the following steps: uniformly mixing bismuth salt and ammonium metavanadate with a surfactant respectively, and roasting through a hydrothermal method and a template effect of the surfactant to prepare the bismuth vanadate material with high specific surface area for electroreduction of carbon dioxide. In carbon dioxide electroreduction, the catalyst has catalytic performance of high activity, good stability and high selectivity and electrochemical performance of low overpotential and high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of carbon dioxide electroreduction, and in particular relates to a bismuth vanadate material for carbon dioxide electroreduction, a preparation method and an application thereof. Background Art

[0002] With the rise of social productivity, the demand and use of fossil fuels is increasing. This not only leads to large amounts of carbon dioxide emissions, causing numerous environmental problems such as the greenhouse effect, but also exacerbates energy consumption, posing a potential energy crisis. Synthesizing different carbon products from carbon dioxide and water, allowing renewable electricity to be directly converted into valuable chemical feedstocks or fuels, thereby closing the anthropogenic carbon cycle, is of great significance. The main methods for producing formic acid include the sodium formate method, the formamide method, and the liquid-phase oxidation of butane (light oil), all of which suffer from high energy consumption and severe pollution. Therefore, the technology of producing formic acid through the electroreduction of carbon dioxide has attracted considerable attention.

[0003] Currently, most catalysts used for the electroreduction of carbon dioxide to formic acid are non-precious metal catalysts. These catalysts are inexpensive and abundant, but previous reports have often encountered issues such as high overpotentials, low current densities, and low Faradaic efficiencies, significantly limiting their potential. In the field of catalysis, it is generally believed that a catalyst's activity is closely linked to its active sites, so a larger surface area increases the number of active sites, thereby improving performance.

[0004] While non-precious metal catalysts used in the electroreduction of carbon dioxide to formic acid offer the advantages of low price and abundant reserves, they are generally limited by high overpotential, low current density, and low Faradaic efficiency. Furthermore, catalytic activity is closely related to the number of active sites, requiring enhanced performance by increasing specific surface area. There is an urgent need to identify catalysts that are economical in raw materials, simple in preparation, suitable for large-scale industrial production, and capable of achieving high specific surface area, high catalytic activity, and excellent electrochemical performance, thereby addressing the shortcomings of existing catalyst technologies, including insufficient performance, high preparation costs, and complex processes. Summary of the Invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a bismuth vanadate material, a preparation method and an application for carbon dioxide electroreduction, so as to solve the technical problems of existing non-precious metal catalysts having high overpotential, low current density, low Faraday efficiency and the need to increase the specific surface area to increase the active sites.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing a bismuth vanadate material for carbon dioxide electroreduction, comprising the following steps: Dissolving a bismuth salt in a nitric acid aqueous solution, adding a first surfactant, and reacting by stirring once to obtain a mixed solution A; Dissolve ammonium metavanadate in a sodium hydroxide aqueous solution, add a second surfactant, and react by stirring twice to obtain a mixed solution B; Mixed solution A and mixed solution B are mixed, the pH value is adjusted to neutral, and after three stirring reactions, hydrothermal reactions, washing, drying, and calcination reactions, a bismuth vanadate material for carbon dioxide electroreduction is obtained.

[0007] Preferably, the mass ratio of the bismuth salt to the first surfactant is (2-10):1; the mass ratio of the ammonium metavanadate to the second surfactant is (2-5):1.

[0008] Preferably, the bismuth salt is at least one of bismuth nitrate, bismuth sulfate, bismuth phosphate, bismuth chloride, bismuth bromide and bismuth iodide; the first surfactant is at least one of sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate and polyvinyl pyrrolidone; the second surfactant is at least one of sodium dodecyl sulfonate, sodium dodecylbenzenesulfonate and polyvinyl pyrrolidone.

[0009] Preferably, the pH value is adjusted to neutral using sodium hydroxide solution or nitric acid solution.

[0010] Preferably, the time for the first stirring reaction is not less than 30 min; the time for the second stirring reaction is not less than 30 min; and the time for the third stirring reaction is not less than 1 h.

[0011] Preferably, the conditions of the hydrothermal reaction include: constant temperature reaction at 120-200° C. for 1-6 hours.

[0012] Preferably, the washing conditions include: washing with ethanol and water alternately; the drying methods include: spray drying, direct heating drying, forced air drying, vacuum drying or freeze drying.

[0013] Preferably, the calcination reaction temperature is 200-500° C., and the calcination reaction time is 1-6 hours.

[0014] The present invention also discloses a bismuth vanadate material for carbon dioxide electroreduction, which is prepared by adopting the above-mentioned preparation method of the bismuth vanadate material for carbon dioxide electroreduction.

[0015] The present invention also discloses the use of the bismuth vanadate material for carbon dioxide electroreduction prepared by the above-mentioned preparation method in the electrocatalytic generation of formic acid from carbon dioxide. The bismuth vanadate material for carbon dioxide electroreduction is used as a cathode material for carbon dioxide electroreduction. When the voltage is -1.4 to -2.0 V, the current density is 70 to 110 mA / cm 2; The Faraday efficiency of carbon monoxide is 3.9%~7.9%; the Faraday efficiency of formic acid is 90.5%~95.6%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a bismuth vanadate material for carbon dioxide electroreduction. Bismuth salt and ammonium metavanadate are dissolved in different solvents and a surfactant is added. A staged stirring reaction ensures uniform dispersion of the components, avoiding localized uneven precipitation that may result from direct mixing. The surfactant acts as a template, guiding the bismuth vanadate nanomaterial to form a lamellar structure through molecular self-assembly, significantly increasing the material's specific surface area and providing more active sites for carbon dioxide electroreduction. A neutral environment prevents strong acids and bases from damaging the bismuth vanadate precursor structure, ensuring the production of stoichiometrically accurate, crystal-complete bismuth vanadate nanomaterials and enhancing the stability of their catalytic performance. A hydrothermal reaction promotes the directional growth of the nanomaterial in a high-temperature, high-pressure environment, forming a uniform lamellar structure. The calcination process, through heat-induced crystallization, optimizes the material's crystal form and pore structure, further improving its conductivity and structural stability, making it suitable for the long-term stability requirements of electrocatalytic reactions. By precisely controlling the nanostructure, optimizing the surface chemistry, and reaction conditions, the bismuth vanadate material achieves efficient catalytic performance in carbon dioxide electroreduction, combining the advantages of low cost, ease of scalability, and high selectivity, providing important support for the industrial application of carbon capture and conversion technologies.

[0017] Furthermore, the bismuth salt to surfactant mass ratio (2-10:1) ensures that the surfactant is fully adsorbed on the bismuth salt particle surface to form a stable template structure, while also preventing excessive surfactant from causing nanoparticle agglomeration or difficulty in template removal. Appropriate templating allows for precise control of the bismuth vanadate sheet thickness and porosity, optimizing mass transfer efficiency and electron transport capacity. The ammonium metavanadate to surfactant mass ratio (2-5:1) can be controlled to adjust the lateral size and stacking density of the bismuth vanadate nanosheets, forming a microstructure that is conducive to the adsorption and activation of carbon dioxide molecules, thereby enhancing the selectivity and activity of the catalytic reaction.

[0018] Furthermore, different anions can adjust the ionic strength and pH of the precursor solution, affecting the nucleation rate and growth kinetics of bismuth vanadate, enabling precise control of the nanomaterial sheet morphology and optimizing catalytic performance. Anionic surfactants electrostatically adsorb onto the metal ion surface, forming a negatively charged template layer that inhibits particle aggregation; nonionic surfactants stabilize the nanoparticles through steric hindrance. Both types can regulate the sheet's dispersion and specific surface area.

[0019] Furthermore, pH adjustment using sodium hydroxide or nitric acid solutions is simple, low-cost, and suitable for large-scale production. Neutral conditions prevent structural defects in the bismuth vanadate precursor caused by acid / base corrosion, ensuring a uniform crystal structure and chemical composition in the final material, and improving the reproducibility and stability of the catalytic reaction.

[0020] Furthermore, appropriate stirring time ensures that the bismuth salt, ammonium metavanadate and surfactant are fully mixed to form a uniform sol system, avoiding the broadening of the nanoparticle size distribution due to local uneven concentration, promoting the full reaction of mixed solution A and mixed solution B, forming a stable precursor precipitate, providing a uniform reactant base for the subsequent hydrothermal reaction, and ensuring the morphological uniformity of the bismuth vanadate nanomaterial.

[0021] Furthermore, by optimizing temperature and time, the specific surface area, conductivity, and mechanical strength of the material can be balanced to meet the needs of different electrocatalytic reactions. Small-sized sheets are beneficial for increasing the density of active sites, while large-sized sheets are beneficial for reducing mass transfer resistance.

[0022] Furthermore, alternating ethanol and water washing effectively removes surface-adsorbed templates, ionic impurities, and byproducts, preventing the inhibitory effects of impurities on catalytic activity. Solvent replacement also reduces nanosheet agglomeration during the drying process. A variety of drying methods are available to accommodate varying production scales and equipment requirements. Spray drying is suitable for continuous production, while freeze drying maximizes the preservation of the nanosheet's pore structure, ensuring a high specific surface area and catalytic activity.

[0023] Furthermore, by optimizing the calcination parameters, the surface chemical state of bismuth vanadate can be regulated to further optimize the carbon dioxide adsorption and conversion efficiency.

[0024] The present invention also discloses a bismuth vanadate material for carbon dioxide electroreduction, prepared using the aforementioned method. The material exhibits a high specific surface area, a lamellar porous structure, and a large number of exposed active crystal faces, significantly enhancing its adsorption capacity for carbon dioxide molecules and electron transfer efficiency. Furthermore, the material exhibits high chemical stability and is resistant to deactivation during electrocatalytic reactions, making it suitable for long-term industrial applications.

[0025] The present invention also discloses the application of the bismuth vanadate material for carbon dioxide electroreduction prepared by the above-mentioned preparation method in the electrocatalytic generation of formic acid from carbon dioxide. The high current density indicates that the material has excellent electron transport capability and reaction kinetics, and can achieve efficient carbon dioxide conversion at low overpotential, reducing energy consumption. The high formic acid selectivity indicates that the lamellar structure and surface chemical properties can directionally regulate the reaction path, inhibit the formation of the byproduct CO, improve the purity of the target product formic acid, and reduce subsequent separation costs. The stable catalytic performance at -1.4 to -2.0V indicates that it has strong corrosion resistance, can operate for a long time under industrial-grade electrolysis conditions, and has the potential for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the XRD pattern of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; Figure 2 This is an SEM image of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; Figure 3 This is the LSV curve of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; Figure 4 This is the IT curve of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; Figure 5 This is a magnified SEM image of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. All other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0028] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0029] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0030] In the present invention, unless otherwise specified, percentages (%) or parts refer to percentages by weight or parts by weight relative to the composition.

[0031] In the present invention, unless otherwise specified, the components involved or their preferred components can be combined with each other to form a new technical solution.

[0032] In this disclosure, unless otherwise specified, the numerical range "a-b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6-22" indicates that all real numbers between "6-22" are listed herein, and "6-22" is merely an abbreviation for these numerical combinations.

[0033] The "range" disclosed in the present invention is in the form of lower limit and upper limit, which can be one or more lower limits, and one or more upper limits respectively.

[0034] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0035] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the order. Preferably, the reaction method herein is carried out sequentially.

[0036] Unless otherwise indicated, the professional and scientific terms used herein are the same as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content can also be applied to the present invention.

[0037] The present invention provides a method for preparing a bismuth vanadate material for carbon dioxide electroreduction, comprising the following steps: 1) A bismuth salt is dissolved in a nitric acid aqueous solution, and a certain amount of a surfactant is added. The mixture is stirred at room temperature for at least 30 minutes to obtain a mixed solution A. The mass ratio of the bismuth salt to the surfactant is (2-10):1. The bismuth salt is one or more of bismuth nitrate, bismuth sulfate, bismuth phosphate, bismuth chloride, bismuth bromide, and bismuth iodide. The surfactant is one or more of sodium dodecylsulfonate, sodium dodecylbenzenesulfonate, and polyvinylpyrrolidone.

[0038] 2) Dissolve ammonium metavanadate in aqueous sodium hydroxide solution, add a certain amount of surfactant, and stir at room temperature for at least 30 minutes to obtain a mixed solution B. The mass ratio of ammonium metavanadate to surfactant is (2-5):1.

[0039] 3) Mixing the mixed solution A obtained in step 1) with the mixed solution B obtained in step 2) to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a certain concentration of sodium hydroxide solution or a certain concentration of nitric acid solution, and stirring at room temperature for at least 1 hour to obtain a mixed solution D.

[0040] 4) Transfer the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor and react at a constant temperature of 120-200° C. for 1-6 hours to obtain a precipitate.

[0041] 5) Washing the precipitate obtained in step 4) with ethanol and water, and drying to obtain a powder material. The drying method is any one of spray drying, direct heating drying, forced air drying, vacuum drying, and freeze drying.

[0042] 6) Calcine the powder material obtained in step 5) at a certain temperature and for a certain time in an air atmosphere to obtain a bismuth vanadate material for carbon dioxide electroreduction. The calcination temperature is 200-500° C. and the calcination time is 1-6 hours.

[0043] This method uses a hydrothermal method to utilize the template effect of a surfactant, followed by calcination, to prepare a bismuth vanadate material with a high specific surface area for carbon dioxide electroreduction. The preparation method is simple, low-cost, and easy to implement on a large scale. This catalyst material exhibits high catalytic and electrochemical performance when applied to carbon dioxide electroreduction reactions.

[0044] The present invention also discloses a bismuth vanadate material for carbon dioxide electroreduction, prepared using the above-mentioned preparation method. The lamellar structure formed by the template effect of the surfactant significantly increases the specific surface area of ​​the material. Compared with traditional bulk materials, the lamellar structure allows the active sites to be more exposed to the reaction system, providing abundant sites for the adsorption and activation of carbon dioxide molecules. At the same time, this structure also shortens the diffusion path of reactants and products, improves mass transfer efficiency, and facilitates the rapid progress of the electroreduction reaction. During the hydrothermal and calcination processes, the removal of the surfactant and the pores formed during crystal growth give the bismuth vanadate material a unique porous structure. These pores not only further increase the specific surface area, but also provide gas diffusion channels, allowing carbon dioxide molecules to reach the active sites more smoothly, while also facilitating the rapid desorption of reaction products, reducing product accumulation at the active sites, and maintaining stable catalytic activity. Different preparation conditions, such as calcination temperature and time, can regulate the crystal structure of bismuth vanadate, affecting the adsorption pattern of carbon dioxide molecules and the formation of reaction intermediates, thereby optimizing the reaction path and improving the selectivity and activity of the catalytic reaction. The material's nanoscale size significantly increases the proportion of surface atoms, which possess unsaturated chemical bonds and high surface energy, enhancing the material's adsorption capacity for CO2 molecules and its catalytic activity. Furthermore, the nanoscale size imparts a high density of surface active sites, further improving catalytic efficiency. The abundance of active sites, along with excellent mass transfer and electron transport properties, contribute to the bismuth vanadate's high catalytic activity. In the CO2 electroreduction reaction, it can rapidly promote the activation and conversion of CO2 molecules at relatively low overpotentials, increasing the reaction rate and reducing the required energy input. The unique material structure and surface properties give the bismuth vanadate material high selectivity for target products, such as formic acid. By manipulating the material's microstructure and surface chemical state, the reaction pathway can be directed, side reactions can be suppressed, the Faradaic efficiency of formic acid can be increased, and the cost of subsequent product separation and purification can be reduced, ultimately contributing to improved economic benefits in industrial applications.

[0045] The present invention also discloses the use of the above-mentioned bismuth vanadate material for carbon dioxide electroreduction in the electrocatalytic production of formic acid from carbon dioxide, and the method of use comprises the following steps: 1) Grind the prepared bismuth vanadate material for carbon dioxide electroreduction, take 0.015 g and dissolve it in 1-3 mL of solvent to obtain a mixed solution; 2) adding a certain amount of 5 wt% Nafion solution to the mixed solution obtained in step 1) and stirring vigorously for at least 24 hours; 3) Spray 300 μL of the solution obtained in step 2) onto carbon paper as the cathode material; 4) It is applied in a carbon dioxide electroreduction system using 0.1M KHCO3 aqueous solution as the electrolyte.

[0046] The design principles of the present invention are as follows: Bismuth salt and ammonium metavanadate are uniformly mixed with surfactants, stirred for a certain period of time, and then mixed together. Using the template effect of the surfactant, a hydrothermal method is used to prepare a lamellar bismuth vanadate nanomaterial with a high specific surface area after calcination. This material is then used in carbon dioxide electroreduction.

[0047] The present invention utilizes a mixture of different bismuth salts and surfactants to prepare a series of nanomaterials with different precursors. By varying the hydrothermal reaction temperature and time, lamellar bismuth vanadate nanomaterials of varying sizes are obtained. The raw materials used are inexpensive, the preparation method is simple, low-cost, and easy to operate, making it suitable for large-scale industrial production. The prepared bismuth vanadate materials for carbon dioxide electroreduction exhibit high catalytic activity, good stability, and high selectivity, as well as electrochemical properties with low overpotential and high current density.

[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0049] Example 1 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 1.75 g of bismuth nitrate in 10 ml of 4 M nitric acid solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution A. 2) Dissolve 0.88 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution B; 3) Mixing the mixed solution A obtained in steps 1) and 2) with the mixed solution B to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, and stirring at room temperature for 1 hour to obtain a mixed solution D.

[0050] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 200° C. for 2 h to obtain a precipitate; 5) The precipitate obtained in step 4) is washed with ethanol and water, and directly heated to dryness.

[0051] 6) The powder material obtained in step 5) was heated to 400° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 2 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which was numbered BiVO4-1.

[0052] Figure 1 This is the XRD spectrum of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; it can be seen from the figure that the characteristic diffraction peaks of the sample can perfectly match those of monoclinic bismuth vanadate (JCPDF#14-0688) and there are no other impurity peaks, and the peaks with 2θ of 18.6°, 28.87°, 30.53°, 42.35° and 53.24° correspond to the (110), (-121), (040), (150) and (161) crystal planes of bismuth vanadate, respectively. At the same time, its diffraction peaks are sharp, which proves that the obtained bismuth vanadate material has good crystallinity.

[0053] Figure 2 This is an SEM image of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; as can be seen from the figure, the bismuth vanadate material has a lamellar structure with relatively uniform size, showing the microscopic morphology of two-dimensional lamellar bismuth vanadate.

[0054] Figure 3 This is the LSV curve of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention. As can be seen from the figure, when the catalyst is tested in the voltage range of -0.5 to -1.1 V vs. RHE at a scan rate of 1 mV / s, the cathode current density of bismuth vanadate increases rapidly with increasing voltage from -0.6 V vs. RHE, reaching -107.5 mA cm at -1.0 V vs. RHE. -2 , indicating that bismuth vanadate materials have excellent carbon dioxide electroreduction activity.

[0055] Figure 4 This is the IT curve of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention. As can be seen from the figure, when the applied voltage is -1.0 V vs. RHE, the current density of bismuth vanadate can be stably maintained at -110 mA cm for a long time. -2 , indicating that the bismuth vanadate catalyst has excellent carbon dioxide electroreduction activity and good stability.

[0056] Figure 5 This is a magnified SEM image of the bismuth vanadate material for carbon dioxide electroreduction provided in Example 1 of the present invention; as can be seen from the figure, the bismuth vanadate material presents an irregular lamellar morphology with a rough surface and multiple sharp edges and protrusions.

[0057] Example 2 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 1.75 g of bismuth nitrate in 10 ml of 4 M nitric acid solution, add 0.25 g of polyvinyl pyrrolidone, and stir at room temperature for 30 minutes to obtain a mixed solution A. 2) Dissolve 0.88 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of polyvinyl pyrrolidone, and stir at room temperature for 30 minutes to obtain a mixed solution B; 3) Mixing the mixed solution A obtained in steps 1) and 2) with the mixed solution B to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, and stirring at room temperature for 1 hour to obtain a mixed solution D.

[0058] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 200° C. for 2 h to obtain a precipitate; 5) The precipitate obtained in step 4) was washed with ethanol and water and dried.

[0059] 6) The powder material obtained in step 5) was heated to 400° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 2 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which was numbered BiVO4-2.

[0060] Example 3 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 1.75 g of bismuth nitrate in 10 ml of 4 M nitric acid solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution A. 2) Dissolve 0.88 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution B; 3) Mixing the mixed solutions A and B obtained in steps 1) and 2) to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, and stirring at room temperature for 1 hour to obtain a mixed solution D.

[0061] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 150° C. for 2 h to obtain a precipitate; 5) The precipitate obtained in step 4) was washed with ethanol and water and dried.

[0062] 6) The powder material obtained in step 5) is heated to 400° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 2 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which is numbered BiVO4-3.

[0063] Example 4 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 1.75 g of bismuth nitrate in 10 ml of 4 M nitric acid solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution A. 2) Dissolve 0.88 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution B; 3) Mixing the mixed solutions A and B obtained in steps 1) and 2) to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, and stirring at room temperature for 1 hour to obtain a mixed solution D.

[0064] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 200° C. for 6 h to obtain a precipitate; 5) The precipitate obtained in step 4) was washed with ethanol and water and dried.

[0065] 6) The powder material obtained in step 5) was heated to 400° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 2 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which was numbered BiVO4-4.

[0066] Example 5 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 1.75 g of bismuth nitrate in 10 ml of 4 M nitric acid solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution A. 2) Dissolve 0.88 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 30 minutes to obtain a mixed solution B; 3) Mixing the mixed solutions A and B obtained in steps 1) and 2) to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, and stirring at room temperature for 1 hour to obtain a mixed solution D.

[0067] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 200° C. for 2 h to obtain a precipitate; 5) The precipitate obtained in step 4) was washed with ethanol and water and dried.

[0068] 6) The powder material obtained in step 5) was heated to 300° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 2 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which was numbered BiVO4-5.

[0069] Example 6 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 1.75 g of bismuth sulfate in 10 ml of 4 M nitric acid solution, add 0.125 g of sodium dodecylbenzenesulfonate and 0.125 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 35 minutes to obtain a mixed solution A; 2) Dissolve 0.88 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.125 g of sodium dodecylbenzenesulfonate and 0.125 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 35 minutes to obtain a mixed solution B; 3) Mixing the mixed solution A obtained in steps 1) and 2) with the mixed solution B to obtain a mixed solution C. Adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, stirring at room temperature for 1.5 hours, and obtaining a mixed solution D.

[0070] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 120° C. for 5 h to obtain a precipitate; 5) The precipitate obtained in step 4) is washed with ethanol and water, and directly heated to dryness.

[0071] 6) The powder material obtained in step 5) is heated to 200° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 6 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which is numbered BiVO4-6.

[0072] Example 7 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 0.5 g of bismuth phosphate in 10 ml of 4 M nitric acid solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 40 minutes to obtain a mixed solution A. 2) Dissolve 0.5 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 40 minutes to obtain a mixed solution B; 3) Mixing the mixed solution A obtained in steps 1) and 2) with the mixed solution B to obtain a mixed solution C. Adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, stirring at room temperature for 1.5 hours, and obtaining a mixed solution D.

[0073] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 160° C. for 4 h to obtain a precipitate; 5) The precipitate obtained in step 4) is washed with ethanol and water, and directly heated to dryness.

[0074] 6) The powder material obtained in step 5) was heated to 300° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 4 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which was numbered BiVO4-7.

[0075] Example 8 A method for preparing a bismuth vanadate material for carbon dioxide electroreduction comprises the following steps: 1) Dissolve 2.5 g of bismuth chloride in 10 ml of 4 M nitric acid solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 45 minutes to obtain a mixed solution A. 2) Dissolve 1.25 g of ammonium metavanadate in 10 ml of 2 M sodium hydroxide solution, add 0.25 g of sodium dodecylbenzenesulfonate, and stir at room temperature for 45 minutes to obtain a mixed solution B; 3) Mixing the mixed solution A obtained in steps 1) and 2) with the mixed solution B to obtain a mixed solution C, adjusting the mixed solution C to neutrality with a 2M sodium hydroxide solution and a 4M nitric acid solution, and stirring at room temperature for 2 hours to obtain a mixed solution D.

[0076] 4) Transferring the mixed solution D obtained in step 3) to a polytetrafluoroethylene-lined reactor, and reacting at 180° C. for 1 h to obtain a precipitate; 5) The precipitate obtained in step 4) is washed with ethanol and water, and directly heated to dryness.

[0077] 6) The powder material obtained in step 5) is heated to 500° C. at a heating rate of 10° C. / min in an air atmosphere and calcined for 1 h to obtain a bismuth vanadate material for carbon dioxide electroreduction, which is numbered BiVO4-8.

[0078] Example 9 The difference from Example 1 is that the bismuth salt is bismuth bromide.

[0079] Example 10 The difference from Example 1 is that the bismuth salt is bismuth iodide.

[0080] Example 11 Different from Example 1, the bismuth salt is bismuth iodide and bismuth bromide in a mass ratio of 1:1.

[0081] In order to investigate the performance of the bismuth vanadate material for carbon dioxide electroreduction in carbon dioxide electroreduction applications, the bismuth vanadate material for carbon dioxide electroreduction prepared in Examples 1 to 5 was used as the cathode material for carbon dioxide electroreduction testing and was tested in a gas diffusion electrolysis cell system. First, a cathode slurry was prepared. 15 mg of the bismuth vanadate material for carbon dioxide electroreduction prepared in Examples 1 to 5 was dissolved in 2 ml of anhydrous ethanol, and 200 μL of a 5 wt% Nafion solution was added. The three were evenly mixed together, and 300 μL was sprayed on carbon paper to obtain a cathode material.

[0082] Finally, the above cathode materials were tested, using commercial iridium carbon as the anode material and potassium bicarbonate as the electrolyte, with a voltage range of -1.4 to -2.0 V. The test results at -1.7 V are shown in Table 1: Table 1 Test results of carbon dioxide electroreduction performance of bismuth vanadate materials for carbon dioxide electroreduction prepared in Examples 1 to 5

[0083] Table 1 shows the carbon dioxide electroreduction performance test results of the bismuth vanadate materials for carbon dioxide electroreduction prepared in Examples 1 to 5. As can be seen from Table 1, the bismuth vanadate material for carbon dioxide electroreduction provided by the present invention is used as a cathode material for carbon dioxide electroreduction, with a current density of 70 to 110 mA / cm2; a carbon monoxide Faraday efficiency of 3.9% to 7.9%; and a formic acid Faraday efficiency of 90.5% to 95.6%. It has high current density, high formic acid selectivity, and high stability.

[0084] In summary, the present invention provides a bismuth vanadate material for carbon dioxide electroreduction, a preparation method, and an application thereof. The preparation method is simple, and a precursor and a surfactant are evenly mixed, and the material can be prepared by a simple hydrothermal reaction. After programmed temperature rise, a bismuth vanadate material for carbon dioxide electroreduction is obtained. The catalyst is applied to the carbon dioxide electroreduction reaction to prepare formic acid, has excellent catalytic activity and electrochemical properties, and can be applied in industrial production.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a bismuth vanadate material for carbon dioxide electroreduction, characterized in that: The following steps are involved: Dissolving a bismuth salt in a nitric acid aqueous solution, adding a first surfactant, and reacting by stirring once to obtain a mixed solution A; Dissolve ammonium metavanadate in a sodium hydroxide aqueous solution, add a second surfactant, and react by stirring twice to obtain a mixed solution B; Mixed solution A and mixed solution B are mixed, the pH value is adjusted to neutral, and after three stirring reactions, hydrothermal reactions, washing, drying, and calcination reactions, a bismuth vanadate material for carbon dioxide electroreduction is obtained.

2. The method for preparing a bismuth vanadate material for carbon dioxide electroreduction according to claim 1, wherein: The mass ratio of the bismuth salt to the first surfactant is (2-10):1; the mass ratio of the ammonium metavanadate to the second surfactant is (2-5):

1.

3. The method for preparing a bismuth vanadate material for carbon dioxide electroreduction according to claim 1, wherein: The bismuth salt is at least one of bismuth nitrate, bismuth sulfate, bismuth phosphate, bismuth chloride, bismuth bromide and bismuth iodide; the first surfactant is at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone; the second surfactant is at least one of sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone.

4. The method for preparing a bismuth vanadate material for carbon dioxide electroreduction according to claim 1, wherein: Adjust the pH to neutral using sodium hydroxide solution or nitric acid solution.

5. The method for preparing bismuth vanadate material for carbon dioxide electroreduction according to claim 1, wherein: The time for the first stirring reaction is no less than 30 minutes; the time for the second stirring reaction is no less than 30 minutes; and the time for the third stirring reaction is no less than 1 hour.

6. The method for preparing bismuth vanadate material for carbon dioxide electroreduction according to claim 1, characterized in that: The conditions of the hydrothermal reaction include: constant temperature reaction at 120-200° C. for 1-6 hours.

7. The method for preparing bismuth vanadate material for carbon dioxide electroreduction according to claim 1, characterized in that: The washing conditions include: washing with ethanol and water alternately; the drying methods include: spray drying, direct heating drying, blast drying, vacuum drying or freeze drying.

8. The method for preparing bismuth vanadate material for carbon dioxide electroreduction according to claim 1, characterized in that: The calcination reaction temperature is 200-500° C., and the calcination reaction time is 1-6 hours.

9. A bismuth vanadate material for carbon dioxide electroreduction, characterized in that: The bismuth vanadate material is prepared by the preparation method of any one of claims 1 to 8 for electroreduction of carbon dioxide.

10. Use of the bismuth vanadate material for carbon dioxide electroreduction prepared by the preparation method according to any one of claims 1 to 8 in the electrocatalytic production of formic acid from carbon dioxide, characterized in that: The bismuth vanadate material for carbon dioxide electroreduction is used as a cathode material for carbon dioxide electroreduction. When the voltage is -1.4 to -2.0 V, the current density is 70 to 110 mA / cm 2 ; The Faraday efficiency of carbon monoxide is 3.9%~7.9%; the Faraday efficiency of formic acid is 90.5%~95.6%.

Citation Information

Cited By

  • A method for preparing a hydrophobic conductive fiber catalytic membrane for synthesizing ammonia from flue gas NO

    CN122441500A